2021
DOI: 10.3389/fmicb.2021.745502
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Generation of a Recombinant Senecavirus a Stably Expressing the NanoLuc Luciferase for Quantitative Antiviral Assay

Abstract: Senecavirus A (SVA), also known as Seneca Valley virus, is a recently emerged picornavirus that can cause swine vesicular disease, posing a great threat to the global swine industry. A recombinant reporter virus (rSVA-Nluc) stably expressing the nanoluciferase (Nluc) gene between SVA 2A and 2B was developed to rapidly detect anti-SVA neutralizing antibodies and establish a high-throughput screen for antiviral agents. This recombinant virus displayed similar growth kinetics as the parental virus and remained st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The authors demonstrated that RvJX-Nsp2325-HiBiT can be used as a highly efficient platform for the screening and evaluation of anti-PRRSV therapies by showing that RvJX-Nsp2325-HiBiT is a convenient and stable tool for evaluating viral propagation both in vitro and in vivo. In addition, a recombinant senecavirus A (rSVA) expressing the Nano-Luc gene between SVA 2A and 2B has been established [32]. Based on a comparison of rSVA Nano-Luc with the traditional PRNT50 assay, a new neutralization assay was proposed, and the applicability of rSVA Nano-Luc to antiviral interferon-stimulated gene screening was demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…The authors demonstrated that RvJX-Nsp2325-HiBiT can be used as a highly efficient platform for the screening and evaluation of anti-PRRSV therapies by showing that RvJX-Nsp2325-HiBiT is a convenient and stable tool for evaluating viral propagation both in vitro and in vivo. In addition, a recombinant senecavirus A (rSVA) expressing the Nano-Luc gene between SVA 2A and 2B has been established [32]. Based on a comparison of rSVA Nano-Luc with the traditional PRNT50 assay, a new neutralization assay was proposed, and the applicability of rSVA Nano-Luc to antiviral interferon-stimulated gene screening was demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Nluc has been inserted to an EV71 infectious clone and this EV71-Nluc virus is genetically stable and confers stable luciferase activity over 10 passages in cultured cells ( Yang et al, 2021 ), overcoming its shorter lifetime in EV71-Gluc virus ( Xu et al, 2015 ). In another reverse genetic study of Senecavirus A with a insertion of Nluc gene between 2A and 2B, this reporter virus is also stable over 10 passages in BHK-21 cells ( Guo et al, 2021 ). Consistent with these earlier reports, we report here that the rCA16-Nluc virus has been confirmed stable in Vero cells by multiple assays.…”
Section: Discussionmentioning
confidence: 99%
“…Engineered SVV (eSVV) rescue system: The SVV genome has a length of 7.2 kb containing a unique orf flanked by a 5 untranslated region (UTR) and 3 UTR followed by a poly(A) tail [55]. The orf codifies for a single polyprotein that undergoes post-translational modifications by virus-encoded proteases to generate the final protein products (5 -L-VP4-VP2-VP3-VP1-2A-2B-2C-3A-3B-3C-3D-3 ) (Figure 2B) [56].…”
Section: Seneca Valley Virus (Svv)mentioning
confidence: 99%